2022
DOI: 10.1128/spectrum.01658-22
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Candida albicans Infection in Mice Causes Endogenous Endophthalmitis via Breaching the Outer Blood-Retinal Barrier

Abstract: Patients with candidemia often experience endophthalmitis, a blinding infectious eye disease. However, the pathogenesis of Candida endophthalmitis is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Among the causative agents, C. albicans remains a primary contributor to fungal endogenous endophthalmitis, followed by Aspergillus species 10,11 . Recent in vivo research has indicated that systemic Candida albicans infection in mice triggers endogenous endophthalmitis by disrupting the outer blood‐retinal barrier (oBRB) 12 …”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the causative agents, C. albicans remains a primary contributor to fungal endogenous endophthalmitis, followed by Aspergillus species 10,11 . Recent in vivo research has indicated that systemic Candida albicans infection in mice triggers endogenous endophthalmitis by disrupting the outer blood‐retinal barrier (oBRB) 12 …”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…10,11 Recent in vivo research has indicated that systemic Candida albicans infection in mice triggers endogenous endophthalmitis by disrupting the outer bloodretinal barrier (oBRB). 12 In previous studies, vitreoretinal findings were classified into stages: Stage I, characterized by chorioretinal changes without extension to the vitreous cavity; Stage II, where a fungal mass penetrates the inner limiting membrane and buds in the vitreous cavity; Stage III, associated with vitreous opacity leading to unclear fundal observation; and Stage IV, marked by the complication of retinal detachment (RD) concurrent with Stage III. This staging framework helps determine the optimal timing for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the injury group, retinal punches were exposed to hypoxia (2.3% O 2 ) [46][47][48], hyperoxia (40% O 2 ) [49][50][51], hyperthermia (40°C) [52][53][54], hypothermia (33°C) [55][56][57], and methanol poisoning (8 μM formic acid) [58][59][60][61]. In the disease category, retinae were exposed to lipopolysaccharide (LPS, 0.2 μg/mL), mimicking Gram-negative bacterial infection [62][63][64][65]; interferon-γ (1.0 μg/mL), mimicking inflammation [66][67][68]; Candida albicans (100 CFU/mL), mimicking ocular candidiasis [69][70][71][72]; Bartonella henselae (100 CFU/mL), mimicking neuroretinitis [73]; and hyperglycemia (20 mM glucose), mimicking diabetes [74].…”
Section: Cell Type-specific Response To Stress Injury and Disease In ...mentioning
confidence: 99%
“…However, ensuring optimal therapeutic outcomes has frequently involved a comprehensive assessment of the ocular fundus, especially since identifying ocular candidiasis dictates a pivot towards utilizing agents, such as Fluconazole, that traverse the BRB effectively [68,69]. In clinical practice, unaddressed ocular candidiasis is considered a credible threat to patient survival by maintaining a continual source of infection [70]. These common practices are more recently confirmed by recent guidelines about performing ocular fundus evaluations.…”
Section: Systemic Fungal Infectionsmentioning
confidence: 99%